2017
DOI: 10.1186/s12906-017-1854-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities and toxicological study of the aqueous extract from leaves of Alchornea cordifolia (Euphorbiaceae)

Abstract: Background A. cordifolia is a plant widely used in Africa to solve many health problems. In Cameroon, it is used in the treatment of urogenital infections. As a continuation of our search for pharmacologically active agents from natural sources, the antimicrobial activity of A. cordifolia leaf extracts against E. coli and the toxicity of this extract were investigated.MethodsThe antibacterial activity of the aqueous extract from leaves of Alchornea cordifolia was carried out in vitro on Escherichia coli, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
2
9
1
2
Order By: Relevance
“…The extracts of Alchornea cordifolia are those containing all ten groups of secondary metabolites sought. This result is the same as those obtained by a large number of studies where Alchornea cordifolia, thanks to its wide range of active ingredients, would be used as a panacea in several African countries and for the treatment of diseases of different orders [41,35]. In contrast to this study, saponins and alkaloids are absent in the aqueous extract of Alchornea cordifolia [34].…”
Section: Discussionsupporting
confidence: 89%
“…The extracts of Alchornea cordifolia are those containing all ten groups of secondary metabolites sought. This result is the same as those obtained by a large number of studies where Alchornea cordifolia, thanks to its wide range of active ingredients, would be used as a panacea in several African countries and for the treatment of diseases of different orders [41,35]. In contrast to this study, saponins and alkaloids are absent in the aqueous extract of Alchornea cordifolia [34].…”
Section: Discussionsupporting
confidence: 89%
“…In this experiment, we set three double ratio concentration 20 mg/kg, 40 mg/kg, and 80 mg/kg. The acute toxicity study for anthraquinones (emodin) showed LD 50 values of 8.6 g/kg and 3.8 g/kg in male and female mice, respectively (Djimeli et al, 2017), which is much higher than the three concentrations in our experiment.…”
Section: Resultscontrasting
confidence: 62%
“…Treatment of this disease requires in most cases a combination of several molecules with specific mechanisms of action. This treatment has 4 goals: relieve pain, accelerate healing, prevent complications and reduce the frequency of relapses (Brzozowski et al, 2002;Takezomo et al, 2004).The effective treatment using conventional medicines is not usually well attended by patients, due to their high cost and low availability to a large majority of the population, especially those living in rural areas (Awoussong et al, 2015;Djimeli et al, 2017. In many developing countries, the health infrastructure is poor and a large majority of the population, mainly rural, has no access to primary health care and modern medicines (Kumar et al, 2008;Fokunang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%